Operational Cost Efficiency and Profitability Effects on Companies Distribution Stock Prices During Covid-19 - Putra, Raden Aditya Kristamtomo; Fadil Persada, Satria; Devi Kumalasari, Riesta; Mira Herdina, Ajeng; Sekardhani, Mufida; Razif, Mohammad (Jurnal Manajemen Teknologi, 2024)
Abstract. This study was conducted to determine whether the efficiency of operating costs and profitability of companies listed on the Indonesia Stock Exchange in the banking sector on stock prices. Research design, data, and methodology: This study uses 35 banking companies from 2020 to 2021 as a sample in the study, with a total of 70 financial statements data. The analysis test was conducted to see the effect of operational cost efficiency and profitability on stock prices in banking companies during the covid-19 pandemic. Multiple linier regression is conducted to check the simultaneous test and partial test. As for the indicators in cost efficiencies are operating expenses on operating income. The profitability effects indicators are based on return on equity. Stock prices indicators are based on internal and external policies and abilities. The test results show that operational cost efficiency and profitability have a simultaneous effect on stock prices. However, it partially shows that operational cost efficiency has no significant effect. Meanwhile, profitability shows positive results and has a significant effect. Conclusions: Based on the table of the Coefficient of Determination (R²) test, the value of Adjusted R Square is 98.7%. This shows that the variables of Operational Cost Efficiency and Profitability affect the stock price by 98.7% and the remaining 1.3% is influenced by other variables. Practical perspectives are further discussed in the paper.   Keywords: Operation cost efficiency, profitability effects, stock prices, multiple linier regression, banking sector   Abstrak. Penelitian ini dilakukan untuk mengetahui apakah efisiensi biaya operasional dan profitabilitas perusahaan yang terdaftar di Bursa Efek Indonesia di sektor perbankan terhadap harga saham. Desain penelitian, data, dan metodologi: Penelitian ini menggunakan 35 perusahaan perbankan dari tahun 2020 hingga 2021 sebagai sampel dalam penelitian, dengan total 70 data laporan keuangan. Uji analisis dilakukan untuk melihat pengaruh efisiensi biaya operasional dan profitabilitas terhadap harga saham di perusahaan perbankan selama pandemi covid-19. Regresi linier berganda dilakukan untuk memeriksa uji simultan dan uji parsial. Adapun indikator dalam efisiensi biaya adalah biaya operasional pada pendapatan operasional. Indikator efek profitabilitas didasarkan pada pengembalian ekuitas. Indikator harga saham didasarkan pada kebijakan dan kemampuan internal dan eksternal. Hasil pengujian menunjukkan bahwa efisiensi biaya operasional dan profitabilitas berpengaruh simultan terhadap harga saham. Namun, sebagian menunjukkan bahwa efisiensi biaya operasional tidak berpengaruh signifikan. Sementara itu, profitabilitas menunjukkan hasil positif dan berpengaruh signifikan. Kesimpulan: Berdasarkan tabel uji Coefficient of Determination (R²), nilai Adjusted R Square adalah 98,7%. Hal ini menunjukkan bahwa variabel Efisiensi Biaya Operasional dan Profitabilitas mempengaruhi harga saham sebesar 98,7% dan sisanya 1,3% dipengaruhi oleh variabel lainnya. Perspektif praktis dibahas lebih lanjut dalam penelitian ini. Kata kunci: Efisiensi biaya operasi, efek profitabilitas, harga saham, regresi linier berganda, sektor perbankan